Bartonella spp. and hematological changes in privately owned domestic cats from Rio de Janeiro, Brazil - Aline Moreira Souza; Nadia Regina Pereira Almosny; Alexsandra Rodrigues Mendonça Favacho; Daniele Nunes Pereira Almeida; Renata Fernandes Ferreira; Eliane Oliveira Ferreira; Namir Santos Moreira; Elba Regina Sampaio Lemos (Journal of Infection in Developing Countries)
Introduction: Bartonella infection in cats can represent a risk to owners, particularly today when considering the increase in cat populations and their role in human bartonellosis epidemiology. In the present study, we aimed to detect Bartonella spp. in blood samples from 163 asymptomatic privately-owned cats from the metropolitan area of Rio de Janeiro State, Brazil by using a conventional PCR test and also to evaluate the association between Bartonella spp. and hematological changes in positive cats.